Assembly of Long‐Adapter Single‐Strand Oligonucleotide (LASSO) Probes for Massively Parallel Capture of Kilobase Size DNA Targets. Issue 11 (22nd November 2021) - Chkaiban, Lamia; Tosi, Lorenzo; Parekkadan, Biju
Abstract: Genome DNA sequencing has become an affordable means to resolve questions about the genetic background of life. However, the biological functions of many DNA‐encoded sequences are still relatively unknown. A highly scalable and cost‐effective cloning method to select natural DNA targets from genomic templates is therefore urgently needed to enable rapid understanding of the biological products of genomes. One such method involves LASSO probes, which are long single‐stranded DNA oligonucleotides designed with a universal adapter that is used to link two sequences that are complementary to a genomic target of interest. Through a pooled assembly method, LASSOs can be made for multiplex DNA capture. Herein, we describe a robust, efficient method to assemble LASSO probe libraries using a Cre‐recombinase‐mediated reaction and a protocol for multiplex genome target capture. The starting components are a pre‐LASSO probe library comprising short DNA oligo pools designed in silico and an Escherichia coli plasmid (pLASSO) that incorporates the pre‐LASSO library. Through internal recombination of pLASSO with its inserts, a mature LASSO library in final configuration can be made with high purity. Assembly of a LASSO probe library takes 4 days, and target capture can be performed in a single day. With an exponentially growing list of new genomes available for investigation, this method can enable the rapid production of ORFeome libraries for high‐throughput screening to identify biological functions as a complementary approach to understand genome functional biology. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Assembly of LASSO probes Support Protocol 1 : Generation of pLASSO vectors Support Protocol 2 : Preparation of pre‐LASSOs Basic Protocol 2 : Massively parallel capture of large DNAs using LASSO probes